A 62-Year-Old Woman with Oropharyngeal Disphagia et Causa Epiglottic Inversion Dysfunction - Sabrina, Nabila Wanda; Nugroho, Kristiyanto Aryo; Adji, Iwan Setiawan (Universitas Muhammadiyah Surakarta, 2024)
Purpose: The purpose of this report is to present a case of a left maxillary abscess in a 62-year-old woman, analyze its etiology, risk factors, clinical symptoms, diagnostic examinations, and the treatment provided. This report also highlights the importance of prevention and proper management to improve patient prognosis. Methodology: The methodology used in this report is a clinical case study. Data were collected through anamnesis, physical examination, and supporting examinations such as CT scan and histopathology. The patient's management was analyzed based on existing medical theories and appropriate treatment was provided according to the patient's condition. Results: The patient was diagnosed with oropharyngeal disphagia, presenting with difficulty swallowing since 3 weeks ago.Nasal Endoscopy (NE) examination, the results showed that the epiglottis movement tended to be slow and the conclusion was that dysphagia ec suspect Epiglottic Inversion dysfyntion.The patient received vitamin B12 supplements, the patient showed significant improvement, then given omeprazole/24 hours, paracetamol/8 hours and a high-calorie, high-protein diet (TKTP) both of which were identified as significant risk factors for developing the condition. Applications/Originality/Value: This report provides insights into the importance of early diagnosis and proper management in oropharyngeal dysphagia cases.The findings can be useful for healthcare professionals to understand clinical signs and effective treatment approaches for similar cases.The study emphasizes the need for preventive measures, such as maintaining good oral hygiene and avoiding risk factors like smoking.